Towards Resilient Societies: The Synergy of Religion, Education, Health, Science, and Technology : Proceedings of the International Conference on Innovative Interdisciplinary Science for Inclusive and Sustainable Future (GreenThink 2024), Jakarta, Indonesia, September 12th—13th, 2024 (Volume 1) - Maila D.H. Rahiem (CRC Press, 2026)
Resilience and sustainability are essential in navigating today's global challenges. Towards Resilient Societies: The Synergy of Religion, Education, Health, Science, and Technology presents innovative interdisciplinary research that explores how diverse fields contribute to building adaptive and inclusive communities. This book highlights the intersections of governance, education, health, science, technology, social transformation, and ethical perspectives in achieving sustainable development.This proceedings publication features 164 peer-reviewed papers by scholars all over the world, and delves into seven key themes: education and psychology in resilience-building; governance and political transformation; economic and legal frameworks for sustainability; scientific and technological advancements for societal resilience; religion, ethics, and sustainability; language, communication, and humanities in cultural and social sustainability; and gender equity and inclusive development. By integrating these themes, the book aligns with the United Nations Sustainable Development Goals (SDGs) and provides theoretical and practical insights for shaping a sustainable future.This is an essential resource for academics, researchers, policymakers, and professionals in sustainability, governance and development studies, science and technology, education and health, and social sciences. It offers evidence-based insights and strategic recommendations for fostering more resilient and equitable societies.The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.